Performance of DNA methylation and blood-borne tumor indicators in detecting colorectal neoplasia and adenomas: a comparative study with the fecal occult blood test - Chen, Ming; Zhang, Ji; Xu, Bin; Yao, Bilian; Wang, Zhenzhen; Chen, Ying; Cai, Kaiyu; Zhang, Chenli (Frontiers in Oncology, 2024)
ObjectivesTo evaluate the performance of stool methylated syndecan2 (mSDC2), methylated septin9 (mSEPT9), fecal occult blood test (FOBT), carcinoembryonic antigen (CEA), carbohydrate antigen 125 (CA125) and carbohydrate antigen 199 (CA199) in detecting colorectal neoplasia and adenomas.MethodsBlood-borne CEA, CA125, and CA199 levels were measured by electrochemiluminescence. The SDC2 methylation was detected by Methylation Detection Kit for Human SDC2 Gene (Real time PCR), and the SEPT9 methylation was detected by the Septin9 Gene Methylation Detection Kit based on PCR fluorescent probe assay. The colonoscopy combined with tissue biopsy pathology was used as a validation criterion for colorectal neoplasia.ResultsIn detecting colorectal neoplasia, the AUCs of mSDC2, FOBT and mSEPT9 were 0.935 (95% CI: 0.915-0.956, P<0.001), 0.824 (95% CI: 0.617-1.000, P<0.001) and 0.671 (95% CI: 0.511-0.831, P<0.001), respectively. The sensitivity of mSDC2, FOBT and mSEPT9 were 100.0%, 66.7% and 40.0%, respectively. But the AUC of CEA, CA125 and CA199 were not statistically significant for colorectal neoplasia (all P>0.05). The combined application of mSEPT9 and mSDC2 showed the best predictive performance (AUC: 0.956, 95% CI: 0.887~1.000). For adenomas, the AUC of FOBT was extremely low (AUC: 0.524, 95% CI: 0.502-0.545, P=0.004). The CEA, CA125, CA199, mSEPT9 and mSDC2 were not statistically significant in detecting adenomas (all P>0.05).ConclusionsFor individual tests, FOBT and mSDC2 are relatively better indicators for detecting colorectal neoplasia compared to mSEPT9, CEA, CA125 and CA199. The combined form of mSEPT9 and mSDC2 to detect colorectal neoplasia has good predictive performance. However, none of these indicators demonstrated significant predictive power for detecting adenomas in our study.